2012
DOI: 10.1007/s10236-012-0538-4
|View full text |Cite
|
Sign up to set email alerts
|

Present and future prolonged drought impacts on a large temperate embayment: Port Phillip Bay, Australia

Abstract: Observations of a large temperate embayment in Victoria, Australia, reveal a sustained climatic shift that occurred in response to a prolonged drought in the region during 1997-2009. Historically, the bay is fresher than the ocean with fresh outflow to the sea. However, the drought has caused substantially elevated salinity and temperatures above adjacent oceanic waters. The bay's capacity to dilute and flush waste discharges to the ocean was also changed. Observed conditions have been numerically modelled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Thus, water visibility would be a major factor on habitat selection but few studies have examined the effect of turbidity in foraging preferences of meso-top predators. Here we showed that the core-ranges of penguins occurred in waters that were less turbid compared to the home-range, which is an area subject to much river runoff (Lee et al, 2012). By foraging in relatively productive waters but with low turbidity and therefore higher light levels, penguins may be optimizing their ability to detect and capture prey.…”
Section: Environmental Differences Between the Home-range And Core-ramentioning
confidence: 88%
See 4 more Smart Citations
“…Thus, water visibility would be a major factor on habitat selection but few studies have examined the effect of turbidity in foraging preferences of meso-top predators. Here we showed that the core-ranges of penguins occurred in waters that were less turbid compared to the home-range, which is an area subject to much river runoff (Lee et al, 2012). By foraging in relatively productive waters but with low turbidity and therefore higher light levels, penguins may be optimizing their ability to detect and capture prey.…”
Section: Environmental Differences Between the Home-range And Core-ramentioning
confidence: 88%
“…These regions are enriched in nutrients and are subsequently highly productive in terms of primary productivity (Lee et al, 2012). Given the high primary productivity in this region we would expect penguins to intensively forage in these productive areas.…”
Section: Environmental Differences Between the Home-range And Core-ramentioning
confidence: 99%
See 3 more Smart Citations